A recuperação judicial no ordenamento brasileiro: nova Lei de recuperação judicial e a positividade ou não da constatação prévia junto ao instituto da recuperação judicial no Brasil - Bitencourt, Claudia Martins de (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation has the power to demonstrate and suggest changes in the New Bankruptcy and Corporate Recovery Law (14.112/2020). Where, despite the numerous changes that have taken place, the positivity in the law of prior verification will be punctually addressed here. Where the dysfunctionality of the same and the immobilization of applicability by the magistrates, it will be the main point of defense, because, even having been added after a long time of use without being included in the Law. It only highlighted even more the lack of final decision by the judges, as they are still unable to curb company reorganization requests based on their economic and financial conditions, etc., they only have to analyze the result of the expertise on the legal documental part. The Prior Verification in no way facilitated or reduced the number of procrastinatory demands filed, on the contrary. Thus, in view of this reality, and using an inductive, exemplary analysis, without being exhaustive-conclusive, proclaiming what the misuse of the prerogatives of the Law can cause, based in particular on the new dissertation given to article 51 et seq. of the Judicial Reorganization Law, in which it did not eliminate the gap and the margins of the permanence of obstacles to judges and, finally, the permanence of the Law's dysfunctionality, which must be re-discussed and undergo changes so that the real results can be produced , which magistrates need to be able to work. A situation that urgently requires changes to be made to the New Law, ensuring due process of law with immediate effects, in order to facilitate and give the necessary powers to each judge to curb successful actions before a real and definitive analysis of all essential points of useful life of the company, not just documentary since the distribution of the share. Continuing in this way, only the processes of companies in conditions to recover. Legal change is essential and fundamental for the smooth running of processes and judicial agility before society. With the change, there will be procedural agility, a leaner judiciary, and above all, it will only keep companies that really want and are able to return to the job market. To do so, the Law must be amended, as well as conducting classes, courses, creating manuals on how to act in expert situations and training qualified experts focused on this type of broad analysis.
Keywords: Disfuncionalidade; Constatação prévia; Nova Lei 14.112/20; Positividade ou negatividade da lei; Dysfunctionality; Previous finding; New Law 14.112/20; Positivity or negativity of the law; ACCNPQ::Ciências Sociais Aplicadas::Direito